Physiological fluxes and antioxidative enzymes activities of immobilized Phanerochaete chrysosporium loaded with TiO2 nanoparticles after exposure to toxic pollutants in solution. (June 2015) - Tan, Qiong; Chen, Guiqiu; Zeng, Guangming; Chen, Anwei; Guan, Song; Li, Zhongwu; Zuo, Yanan; Huang, Zhenzhen; Guo, Zhi
Graphical abstract: This paper showed physiological fluxes (H +, O2, and Cd 2+ fluxes) and the antioxidative defense system of PTNs. Highlights: Physiological fluxes of PTNs indicated the instaneous response to 2, 4-DCP and Cd 2+ . H +, O2, and Cd 2+ fluxes of PTNs were measured by the NMT. The antioxidative defense system of PTNs after exposed to Cd 2+ was developed. Abstract: Immobilized Phanerochaete chrysosporium loaded with TiO2 nanoparticles (PTNs) are novel high-value bioremediation materials for adsorbing cadmium and for degrading 2, 4-dichlorophenol (2, 4-DCP). The real-time changes in H + and O2 fluxes were measured using the noninvasive microtest technique (NMT). The H + influx increased after the addition of 2, 4-DCP, and shifted to efflux following the addition of Cd 2+ . The O2 flux decreased after the addition of both 2, 4-DCP and Cd 2+ . A larger Cd 2+ flux was immediately observed after exposure to 0.5 mM Cd 2+ (−351.25 pmol cm −2  s −1 ) than to 0.1 mM Cd 2+ (−107.47 pmol cm −2  s −1 ). The removal of Cd 2+ by the PTNs increased more after treatment with the 0.5 mM exposure solution (27.6 mg g −1 ) than with the 0.1 mM exposure solution (3.49 mg g −1 ). The enzyme activities were analyzed to review the antioxidative defense system of PTNs in a solution containing various concentrations of Cd 2+ . The activities of the coenzyme nicotinamide adenine dinucleotide (NADH) oxidase as well as the enzyme catalase (CAT) plateaued at 6.5 U g −1 FW and 9.7 U g −1 FW, respectively, after exposure to 0.25 mM Cd 2+ . The activity of superoxide dismutase (SOD) increased gradually in solutions containing 0.1–0.6 mM Cd 2+, and eventually reached a maximum (68.86 U g −1 FW). These results illustrate how the antioxidative defense system and the physiological fluxes of PTNs respond to the stress caused by toxic pollutants.